Women’s Right to Maintenance in Legal System of Pakistan with Special Reference to Judgments of Superior Courts - Dr. Hafiz Muhammad Siddique (MEI, 2023)
In Islamic Law, provision of maintenance is the primarily duty of parents particularly the father; sons till the age of majority and daughters till marriage. After marriage, a husband is obliged to maintain his wife during marriage and if divorced till ‘iddah. There are diverse opinions for provision of maintenance after ‘iddah and Pakistani legal system is also silent in this regard. Although, some of the recommendations are under discussion for enacting law on provision of maintenance to a divorcee after ‘iddah till remarriage or during her whole life. Maintenance signifies provision of basic necessities of life to wife that includes food, clothing, lodging and other essential expenses which a husband is liable to provide according to his financial capacity. In Islamic Law, maintenance is considered one of the fundamental rights of a woman and she can dissolve the marriage for provision of non-maintenance. Pakistani law is also providing this right to a wife under section 2, sub-section (ii) of Dissolution of Muslim Marriage Act 1939. The superior judiciary is also playing their role for provision of maintenance during marriage, during ‘iddah period to a divorcee and past maintenance. The current paper discusses the concept of maintenance in Islamic Law and Pakistani law. It also signifies the legitimacy of quantum of maintenance in Islamic Law and legal system of Pakistan. The present paper denotes that in which circumstances wife is entitled for maintenance in Islamic Law by examining the decisions of superior courts. This paper focuses on the examination of judgments of Pakistani superior courts in provision of maintenance to a woman either during her marriage, ‘iddah period or past maintenance and highlights the role of the superior judiciary in protection of woman’s financial right.